Design principles for blockchain and smart contract systems in the energy sector : the case of Finland - Leskinen, Juho (2021)
The energy industry in Europe is in the middle of significant changes as the ambitious plans to reduce carbon emissions are setting new requirements for the energy generation. The development of renewable energy sources has been presented as an environmentally friendly solution to this issue, but due to large proportion of renewable energy generation being weather dependent, the volatility in the energy market is increasing. The volatility issues have increased the demand for more flexible energy system that would be more resistant to the rapid changes in energy generation and consumption levels. European Union (EU) have pursued higher level of harmonization between its member states energy legislation in order to move towards pan-European electricity and energy markets. In addition, Nordic countries are reforming their energy markets through the introductions of data hubs, which are centralised information exchange systems for the electricity retail markets. Presented changes are placing considerable challenges for the Finnish energy sector. This Master’s Thesis explores how blockchain and smart contract systems could be utilized in the Finnish energy sector, and how they could solve the previously presented issues. Blockchain and smart contract systems are emerging technologies that have already demonstrated their benefits regarding automation, in-formation security and process efficiency. Over the last couple of years, these solutions have had growing interest from the energy industry as different blockchain or smart contract-based solutions have been presented. Different pilot projects utilizing blockchain systems have been implemented around Eu-rope and North America. Many of these pilot projects have presented different kinds of peer-to-peer trading systems utilizing blockchain and smart contract systems. Despite of promising results, the possibilities of the technologies in question have not been largely researched in the context of Finnish energy sector. This research paper presents simplified conceptual model of Peer-to-Peer trading in energy community and analysis discussing strengths, weaknesses, opportunities, and threats of blockchain and smart contract systems in the Finnish energy sector.